2018
DOI: 10.3329/jninb.v3i1.36263
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Epilepsy Based on Clinical and Electroencephalographic (EEG) Findings: Experience at Referral Neuroscience Hospital in Bangladesh

Abstract: Background: A good history and a standard EEG recording help establish most of the epilepsy syndromes. Objective: The objective of this study was to establish different epilepsy syndromes on the basis of history and EEG in the clinically suspected seizure events. Methodology: This cross-sectional study was carried out in the neurophysiology laboratory of National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from January 2013 to December 2015, which included 2549 patients. EEG was obtained through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…13 Other studies showed that EEG abnormality was seen in more than 50% of patients. 10,14 Abnormal generalized epileptiform discharge was seen in 11% of our respondents. A study by Joshi revealed abnormal EEG in 43.3% with generalized epilepsy diagnosed on EEG in 26.21% 15 .…”
Section: Discussionmentioning
confidence: 74%
“…13 Other studies showed that EEG abnormality was seen in more than 50% of patients. 10,14 Abnormal generalized epileptiform discharge was seen in 11% of our respondents. A study by Joshi revealed abnormal EEG in 43.3% with generalized epilepsy diagnosed on EEG in 26.21% 15 .…”
Section: Discussionmentioning
confidence: 74%
“…19 In Bangladesh and India, however, generalized seizures outnumbered other types of seizures both in children and adult. 11,17,20 In this light of findings of this study we are further planning a prospective study to be launched soon for further clarifications.…”
Section: Discussionmentioning
confidence: 88%